Ovid’s Shrine in Tomis: Formation and Significance. - Ching-Yuan Wu (Globalizing Ovid: Shanghai 2017. An International Conference in Commemoration of the Bimillennium of Ovid’s Death, 2017)
In the Epistulae ex ponto, Ovid describes how he dealt with the arrival of the silver images of Augustus, Livia and Tiberia that Cotta Messalinus sent him (2.8). He also described his sacrum Caesaris while celebrating the Pomponius brothers for attaining consulships (4.9). The theme of emperor worship as a medium of communication between patrons and their exiled client is striking. Millar noted how Ovid was kept informed of the metamorphoses of the imperial household (Millar 1993, 15-17), and Syme pointed to Ovid’s ability to use concurrent language of homage at Rome (Syme 1978, 167-8). As such, Ovid’s descriptions bear significance beyond proving that domestic worship of living emperors and his household existed (Gradel 2002, 202-203; Martelli 2013, 200).   This paper argues that Ovid’s epistles show how elite Roman society cared about emperor worship. Ovid received the proper set of statues of the imperial family from his friend and patron Cotta Messalinus. He reported to the Pomponius brothers regarding how Tiberius and Livia stant pariter beside the deified Augustus in his sacrum Caesaris, and about his prayers that are meant for public consumption (Price 1984, 92). At stake is his hope to return to Rome: the proper exercise of worship demonstrates not only his pietas but also how he projected imperial symbolism on the edge of the empire. Hence, he boasted how Pontus knew of his pietas as part of his metric resumé submitted to his friend and patron Pomponius Graecinus (Helzle 1989, 22-26). Together with Pliny the Younger’s foundation of a temple at Tifernum (Ep. 10.8), the literary sources offer a potential model for the foundation process of small temples such as the one found at Eretria (Schmid 2001, 113), or others as documented by Simon Price (1984) and Heidi Hänlein-Schäfer (1985).